Russian Federation : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the Russian Federation's growth slowdown that began in 2011, reflecting structural constraints, continued in 2013 despite accommodative policies. Real GDP growth slowed to 1.3 percent owing to a contraction in investment while consumption remained robust owing to strong real wage growth and an unsecured consumer credit boom. The general government balance moved from a modest surplus in 2012 to a deficit of slightly more than 1 percent of GDP in 2013. The IMF staff projects real GDP growth at 0.2 percent in 2014 with considerable downside risks.